The molecular gas content in a protocluster at z = 17: Star formation and AGN feedback. Issue Volume 15:Issue S352(2019) (June 2019) - D'Amato, Q.; Prandoni, I.; Gilli, R.; Massardi, M.; Liuzzo, E.; Mignoli, M.; Vignali, C.; Peca, A.; Nanni, R.
Abstract: A large-scale structure has been recently discovered at z = 1.7, around a powerful FRII radio galaxy. Eight Star Forming Galaxies (SFGs) have been discovered within Δ z ≍ 0.0095 and at < 1 Mpc from the FRII, indicating that this is a signpost of a protocluster. Furthermore, a significant X-ray diffuse emission overlapping the Eastern lobe of the FRII has been detected. Protoclusters are the ideal targets to investigate the complex assembly processes leading to the formation of local galaxy clusters. We will exploit new ALMA CO(2-1) observations (PI: R. Gilli) of the entire region around the FRII galaxy to trace the molecular gas content, in order to discover new protocluster members. Coupling these measurements with the multi-wavelength data coverage available for this field, we aim at placing constrains on the physical conditions in which star formation occurs, and ultimately infer the role of the radio jets in triggering it.